Framing Syrian refugees: US local news and the politics of immigration. (March 2022) - Douai, Aziz; Bastug, Mehmet F; Akca, Davut
The article investigates news coverage and media framing of the Syrian refugee debate as a public opinion issue in US local news in 2015. The sheer number of refugees created an unprecedented humanitarian crisis as millions of civilians settled in neighboring countries, and a significant number of them embarked on a perilous journey to seek refuge in European countries. The political response to the Syrian refugee crisis was divided, but public attitudes shifted after the terrorist attacks on Paris in November 2015 with calls for more restrictive immigration policies and smaller refugee quotas. In the US, GOP leaders demanded "extreme vetting" and "screening" of refugees and many opposed resettling the modest number of refugees the Obama administration promised to let in. The study analyzes local news coverage variation across the States that welcomed, not welcomed or did not commit to accepting Syrian refugees at the height of the Syrian refugee crisis in 2015 and 2016. The findings of the study demonstrate that the editorial framing of the Syrian refugee crisis downplayed the global responsibility and international commitment of the US, highlighted the administrative costs and framed them as security threats. The implications of these frames are discussed.